Agrotourism development strategy during and post Covid-19 pandemic findings from Caping Merapi, Indonesia and Tobwakira Farm, Kiribati - Rozaki, Zuhud; Barnabas, Tearine; Triyono, Triyono; Kamarudin, Mohd Fauzi; Ariffin, Ahmad Shabudin; Ramli, Mona Fairuz (2023)
This research investigates the COVID-19 pandemic impact of Agrotourism between Caping Merapi in Indonesia and Tobwakira Farm in Kiribati. Location determination was carried out purposively at Caping Merapi Agrotourism in Indonesia and Tobwakira Farm Agrotourism in Kiribati. Respondents used in this study were 3 internal parties for both locations, 6 visitors of Caping Merapi and 2 visitors of Tobwakira Farm. The analytical method used is SWOT analysis and IE matrix. This study indicates that Caping Merapi agrotourism faced challenges due to a decrease in the number of visitors and employees, a negative margin of profit, and the low salaries of employees during COVID-19. While Tobwakira Farm faced challenges such as decreased workers and visitors, low salaries for its employees, but income has been achieved due to insufficient importation. Moreover, Caping Merapi's internal total score is 2.96 and its external total score is 2.45, while Tobwakira Farm's internal total score is 2.83 and its external total score is 2.53, indicating the two agrotourism are in cell V, which means growing and maintaining. The SWOT Matrix strategy development strategy for Caping Merapi and Tobwakira Farm includes the following objectives: maintaining and strengthening the characteristics of agrotourism by enhancing the facilities and services, improving human resources in developing consumable products from consumable plants, maximizing promotion in various social media platforms and improve human resources skills in information technology, and conducting online training. In the IE matrix, the development strategy consists of market penetration, product development, and market development.